Menakar Kekuatan Mengikat Putusan Mahkamah Konstitusi dalam Pemberhentian Presiden dan/atau Wakil Presiden di Indonesia - Efendi, Sunarto; Sterigma, Sylli Meliora; Mappuna, Nur Alfitra (Jurnal Konstitusi & Demokrasi, 2024)
Impeachment is a mechanism that allows for the dismissal of a President and/or Vice President before the end of their term. In countries that adopt a presidential system, such as Indonesia, the process and mechanism of impeachment are crucial to regulate, considering the possibility that the President and/or Vice President may commit serious violations or no longer meet the qualifications to regulate a country. This study examines the process and mechanism of dismissing the President and/or Vice President in Indonesia, as well as the ideal framework for such a process. Using a doctrinal legal research method with secondary data from literature studies, the findings show that Indonesia’s impeachment mechanism consists of two stages: a “political process” and a “legal process.” The legal process takes place in the Constitutional Court (MK), where the Court examines, adjudicates, and issues a decision based on the House of Representatives’ (DPR) request for an opinion regarding the impeachment of the President and/or Vice President. However, the Court’s ruling in this matter contradicts the principle of erga omnes—a fundamental characteristic of Constitutional Court decisions—since, in the next stage, there is no obligation for the People’s Consultative Assembly (MPR) to implement the ruling. Therefore, constitutional reforms are needed to strengthen Indonesia’s impeachment process by requiring the People's Consultative Assembly (MPR) in Indonesia to comply with and execute the Constitutional Court’s decision regarding the dismissal of the President and/or Vice President.